Through the Looking-Glass - Lewis Carroll (Kompas Gramedia, 2018)
Alice is playing with a white kitten (whom she calls "Snowdrop") and a black kitten (whom she calls "Kitty") when she ponders what the world is like on the other side of a mirror's reflection. Climbing up onto the fireplace mantel, she pokes at the wall-hung mirror behind the fireplace and discovers, to her surprise, that she is able to step through it to an alternative world. In this reflected version of her own house, she finds a book with looking-glass poetry, "Jabberwocky", whose reversed printing she can read only by holding it up to the mirror. She also observes that the chess pieces have come to life, though they remain small enough for her to pick up